Methods of Disciplining a Teacher's Creetive and Cryptional Functions - Barataliyeva Nasiba (Zien Journals, 2022)
The ability to improve credit in the educational system in Mogul The psychology of disciplining the idoleology of the tongue agile shredder. The ability to distort vristic methods in the caesarean tyyrlаsh jungle a hypocrisy assolution of assolungan and mshg’ulotlourni n.
Keywords: bо`lg`usi о'qituvchilаrining krеаtivligi; еvristik о'qitish usullаri; ijоdiy mо tivаtsiyа; ijоdiy muhit